1988
DOI: 10.1097/00000658-198807000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Stable Prostacyclin Analog on Experimental Ischemie Acute Renal Failure

Abstract: The effect of OP-41483, a stable prostacyclin (PGI2) analog, on ischemic acute renal failure (ARF) was investigated in dogs. Administration of OP-41483 for three days after ischemia significantly increased renal cortical blood flow (RCBF) when compared with dogs treated with the saline vehicle. In the OP-41483-treated group, serum creatinine levels remained relatively low during postoperative days 1-3 and mean survival time was prolonged. Injection of a silicone rubber vascular casting compound (Microfil) reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…A host of other potential vasoconstrictors may be activated and contribute to reduced RBF following I/R injury, including the systemic activation of the sympathetic nervous system, renin-angiotensin II system, endothelin A, prostaglandins, and platelet activating factors. Several studies have been undertaken in which inhibition of these factors provides a partial preservation of RBF and/or GFR and diminishes the severity of AKI [41-52]. However, because vasoconstriction is mediated by a number of redundant pathways, the blockade of any single pathway is not likely to completely protect against injury.…”
Section: Hemodynamic Changesmentioning
confidence: 99%
“…A host of other potential vasoconstrictors may be activated and contribute to reduced RBF following I/R injury, including the systemic activation of the sympathetic nervous system, renin-angiotensin II system, endothelin A, prostaglandins, and platelet activating factors. Several studies have been undertaken in which inhibition of these factors provides a partial preservation of RBF and/or GFR and diminishes the severity of AKI [41-52]. However, because vasoconstriction is mediated by a number of redundant pathways, the blockade of any single pathway is not likely to completely protect against injury.…”
Section: Hemodynamic Changesmentioning
confidence: 99%
“…In this respect, bile salts [8], lactulose [8], antibiotics [2], inhibition of production of prostaglandins [4,9], the preoperative drainage of bile [2], mannitol [10], and dopamine [11] have been used for the prevention of ARF in various clinical and experimental studies. It has been shown that oxygen free radicals play an important role in the pathophysiology of ARF developing after renal ischemia in experimental models [12][13][14][15][16]. We thought that the oxidants may also play a role in the development of renal failure in jaundiced rats by the stimulating effect of endotoxin through the lipoxygenase pathway of arachidonic acid metabolism [17,18], the decrease of antioxydant enzyme activities in volume depletion [16], the disturbances in bodywater compartments in jaundiced patients [10], the increases of reactive oxygen species in jaundice [19,20], and the role of decrease of antioxidant defenses in liver injury in jaundiced rats [21].…”
Section: Introductionmentioning
confidence: 99%
“…Presumably these cells are especially sensitive to a small fall in oxygen delivery [1][2][3]. Decrease in renal blood flow and the redistribution of blood flow from the outer to the inner cortex is seen in bile duct ligated animal models [1,3,4,9]. The profound disturbances of body-fluid compartments and extracellular and intracellular volume depletion have been detected in obstructive jaundice [10].…”
Section: Introductionmentioning
confidence: 99%
“…The prostacyclin receptor distributes to the glomerular cells, endothelial cells, distal tubules, and collecting ducts in human kidney, as shown by the immunohistochemical study using polyclonal antibody against prostacyclin receptor and the in situ hybridization technique [8]. A number of studies have demonstrated the protective effect of prostacyclin in a variety of models for renal injury, including the ischemic acute renal failure in dogs [9]. Although the protective effect of prostacyclin is considered to be due primarily to the vasodilatory action, the direct protective action on renal epithelial cells is demonstrated in hypoxia/reoxygenation injury in a primary culture of rat proximal tubular epithelial cells [10].…”
mentioning
confidence: 99%